Pelatihan canva poster dan iklan kreatif untuk peningkatan literasi digital warga belajar PKBM Bina Kreasi - Wilasari Arien; Viony Syafitra; Nurul Hidayani; Naufal Anshori (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to improve the digital literacy of PKBM Bina Kreasi learners by training them to design promotional posters and short advertisements using Canva. The training involved 25 participants and employed a hands-on approach consisting of feature demonstrations, guided practice, and group-based project assignments. Participants learned to select templates, apply basic principles of layout, typography, and color, and export designs for social media promotion, including the marketing of local micro, small, and medium enterprises (MSMEs). Evaluation was conducted through observation of participants’ products and end-of-session feedback. The results indicate that participants improved their understanding of basic graphic design concepts and their ability to produce visually coherent posters and short promotional videos using Canva. Overall, the activity strengthened participants’ digital literacy and is expected to support broader adoption of digital tools for everyday communication and community-based promotion. PKBM Bina Kreasi, as a non-formal education provider, can also use the outputs to support institutional outreach and recruitment.